Elevated Plasma D-Dimer Level Is Associated With Short-Term Risk of Ischemic Stroke in Patients With Acute Heart Failure. Issue 7 (July 2018) - Hamatani, Yasuhiro; Nagai, Toshiyuki; Nakai, Michikazu; Nishimura, Kunihiro; Honda, Yasuyuki; Nakano, Hiroki; Honda, Satoshi; Iwakami, Naotsugu; Sugano, Yasuo; Asaumi, Yasuhide; Aiba, Takeshi; Noguchi, Teruo; et al.
Abstract : Background and Purpose—: The incidence of heart failure increases the subsequent risk of ischemic stroke, and its risk could be higher in the short-term period after an acute heart failure (AHF) event. However, its determinants remain to be clarified. Plasma D-dimer level reflects fibrin turnover and exhibits unique properties as a biomarker of thrombosis. The aim of this study is to investigate whether D-dimer level is a determinant of short-term incidence of ischemic stroke in patients with AHF. Methods—: We examined 721 consecutive hospitalized AHF patients with plasma D-dimer level on admission from our prospective registry between January 2013 and May 2016. The study end points were incidence of ischemic stroke during hospitalization and at 30 days after admission. Results—: Of the total participants (mean age, 76 years; male, 60%; atrial fibrillation, 54%; mean left ventricular ejection fraction, 38%), in-hospital ischemic stroke occurred in 18 patients (2.5%) during a median hospitalization period of 21 days, and 30-day ischemic stroke occurred in 16 patients (2.2%). Higher D-dimer level on admission was an independent determinant of subsequent risk of in-hospital ischemic stroke even after adjustment by CHA2 DS2 -VASc score (odds ratio, 2.29; 95% confidence interval, 1.46–3.60; P <0.001) or major confounders, including age, atrial fibrillation, and antithrombotic therapy (odds ratio, 2.31; 95% confidence interval, 1.43–3.74; P <0.001). Subgroup analyses showed consistent findings in patients without atrial fibrillation (odds ratio, 2.46; 95% confidence interval, 1.39–4.54; P =0.002) and those without antithrombotic therapy (odds ratio, 2.79; 95% confidence interval, 1.53–5.57; P <0.001). Similar results were obtained for 30-day ischemic stroke as an alternative outcome. Conclusions—: Elevated plasma D-dimer level on admission was significantly associated with increased incidence of ischemic stroke shortly after admission for AHF, suggesting a predictive role of D-dimer for short-term ischemic stroke events in patients with AHF. Clinical Trial Registration—: URL: https://www.umin.ac.jp/ctr/index.htm . Unique identifier: UMIN000017024. Abstract : Supplemental Digital Content is available in the text.